The Fulfillment of Diversion in Cases of Participation in Assault Resulting in Death by Children - Merlin Theodor Handayani Samosir; R. Rahaditya (Journal of Law, Politic and Humanities, 2024)
The increasing number of crimes involving children, the diversion approach is a major concern as an alternative in the juvenile criminal justice system that should be prioritized as mandated by Law No. 11/2012 on Juvenile Criminal Justice System (UU SPPA), which emphasizes peaceful conflict resolution between juvenile offenders and victims. However, this process can be complicated when the victim's family does not accept an amicable settlement. Although peace efforts were achieved between the victim's family and the offender's parents, the difference in sentences between the defendants triggered dissatisfaction and violation of the initial agreement, posing a dilemma in the implementation of diversion. This study highlights the application of diversion in the case resolved in Decision Number 9/Pid.Sus-Anak/2021/PN Jmb, where the peace process between the victim's family and the perpetrator faced challenges, although an agreement was reached. This research uses a normative juridical method with descriptive analysis of legal sources, including laws, journals, and court decisions. The analysis shows that, although diversion is mandatory in juvenile cases, material compensation is not. Its success depends heavily on the willingness of the parties involved to reach a fair and binding agreement so as not to create dilemmas in its implementation. This study recommends refining the diversion mechanism to address conflicts arising from disagreements between the parties in cases of children in conflict with the law.